2021
DOI: 10.3389/fcell.2021.672545
|View full text |Cite
|
Sign up to set email alerts
|

Interkingdom Comparison of Threonine Metabolism for Stem Cell Maintenance in Plants and Animals

Abstract: In multicellular organisms, tissue generation, maintenance, and homeostasis depend on stem cells. Cellular metabolic status is an essential component of different differentiated states, from stem to fully differentiated cells. Threonine (Thr) metabolism has emerged as a critical factor required to maintain pluripotent/multipotent stem cells in both plants and animals. Thus, both kingdoms conserved or converged upon this fundamental feature of stem cell function. Here, we examine similarities and differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 152 publications
1
17
0
Order By: Relevance
“…These observations and manifestations associated with ferritin homeostasis and its turnover are crucial factors to human health and organismal energy balance 54 . So far most of the positive effects of threonine are linked to enhanced immunity, through mucus formation 18,42 , and stimulation of pluripotency of embryonic stem cells [12][13][14][15] . Here, we propose another angle how threonine can achieve health-and lifespan benefits in C. elegans through the attenuation of cellular ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations and manifestations associated with ferritin homeostasis and its turnover are crucial factors to human health and organismal energy balance 54 . So far most of the positive effects of threonine are linked to enhanced immunity, through mucus formation 18,42 , and stimulation of pluripotency of embryonic stem cells [12][13][14][15] . Here, we propose another angle how threonine can achieve health-and lifespan benefits in C. elegans through the attenuation of cellular ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of L-threonine, it was reported that threonine metabolism was a crucial factor for stem cell maintenance and renewal by influencing histone methylation [12][13][14][15] . Moreover, as a major component of mucins, threonine plays a conclusive role in the maintenance of mucosal integrity, barrier constitution, and eventually immune function regulation [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Thr transport and metabolism support stem cell maintenance in both animals and plants, so this reliance on Thr may be an ancient mechanism to conserve stem cell proliferation in multicellular organisms [12]. Similarly, Glu production from Lys seems to support the maintenance of pluripotency in ICM cells of mammalian blastocysts [24], while, in plants, this Glu production regulates their environmental responses and growth [103].…”
Section: Evolutionary Considerationsmentioning
confidence: 99%
“…Thr transporters in eukaryotic stem cells may function as transceptors to help maintain their proliferation [1,12]. Similarly, in most animals, TDH-regulated Thr metabolism, to form Gly and subsequently H3K4me3, likely maintains their pluripotent ES progenitor cells in the ICM [1,12]. In TDH-deficient hES progenitor cells, Gly and H3K4me3 are likely formed from Ser synthesized in the cells [64].…”
Section: Multiple Mechanisms To Maintain Pluripotent Icm Cellsmentioning
confidence: 99%
See 1 more Smart Citation